Pengaruh Stress Kerja Dan Konflik Kerja Terhadap Kinerja Karyawan Melalui Kepuasaan Kerja Sebagai Variabel Intervening : Studi Kasus Pada Karyawan Panglong Karya Dana - Suwadi, Suwadi; Wangi, Putri Sinta (Economic Development Progress, 2023)
This Study Aims To Determine "The Effect Of Work Stress And Conflict On Employee Performance With Job Satisfaction As An Intervening Variable (Case Study Of Employees At Panglong Karya Dana)". This type of research used in research is quantitative. The population in this study were all employees at Panglong Karya Dana. Sampling using census technique. The samples taken were 35 respondents. The analytical tool in this study used the SPSS statistical 25 analysis program. Based on the results of the study, it shows that: 1). Job Stress Variable (X1) affects Job Satisfaction (Z), 2). Work Conflict Variable (X2) has no effect on Job Satisfaction (Z), 3). Job Stress Variable (X1) affects Employee Performance (Y), 4). Work Conflict Variable (X2) affects Employee Performance (Y), 5). Job Satisfaction Variable (Z) effects Employee Performance (Y), 6). Job Satisfaction Variable (Z) cannot mediate the relationship of word Stress (X1) to Employee Performance (Y) as an Intervening Variable, 7). Job Satisfaction Variable (Z) cannot mediate the relationship of word Conflict (X2) to Employee Performance (Y) as an Intervening Variable